2020
DOI: 10.3390/cryst10080636
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Barrier Inhomogeneities and Electronic Transport on Al-Foil/p-Type-4H-SiC Schottky Barrier Diodes Using Diffusion Welding

Abstract: The diffusion welding (DW) is a comprehensive mechanism that can be extensively used to develop silicon carbide (SiC) Schottky rectifiers as a cheaper alternative to existing mainstream contact forming technologies. In this work, the Schottky barrier diode (SBD) fabricated by depositing Al-Foil on the p-type 4H-SiC substrate with a novel technology; DW. The electrical properties of physically fabricated Al-Foil/4H-SiC SBD have been investigated. The current-voltage (I-V) and capacitance-voltage (C-V) character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is noted that non-ideal behaviors (large n TE values compared to ideal unity and big discrepancies between f q Bp TE and f q Bp CV ) are observed for the lightly doped samples. [10][11][12][13] For the highly doped samples, large n TFE values (>1) can also be observed, likely to be ascribed to the tunneling effects by a high doping level. In addition, we found that f q Bp TFE and f q Bp CV are comparable.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is noted that non-ideal behaviors (large n TE values compared to ideal unity and big discrepancies between f q Bp TE and f q Bp CV ) are observed for the lightly doped samples. [10][11][12][13] For the highly doped samples, large n TFE values (>1) can also be observed, likely to be ascribed to the tunneling effects by a high doping level. In addition, we found that f q Bp TFE and f q Bp CV are comparable.…”
Section: Resultsmentioning
confidence: 96%
“…The abnormal behaviors from the TE model for the lightly doped samples are usually ascribed to the barrier inhomogeneities, which may be due to the surface contaminants, subsurface traps, dopant clustering, non-uniform interfacial oxide layer, active defects etc. [10][11][12][13][18][19][20][21][22] It can be speculated that some patches with their low and high local barriers may be embedded in the surrounding of uniform barrier height, 11,23) as schematically shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of barrier height with temperature can be explained by the inhomogeneity at the metal–semiconductor interface. 33,34 The carriers do not have enough energy to surpass the higher energy barrier at low temperatures. As a result, current transport is dominated by current flowing along the channel with the lowest barrier height, increasing the ideality factor.…”
Section: Resultsmentioning
confidence: 99%
“…The last article in the collection also focuses on optimizing Schottky diode technology [8]. It was shown that the diffusion welding (DW) is a comprehensive mechanism that can be extensively used to develop silicon carbide (SiC) Schottky rectifiers as a cheaper alternative to existing mainstream contact forming technologies.…”
mentioning
confidence: 99%